2017
DOI: 10.1017/s0024282917000184
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal patterns of meiospores shape population spatial structure of saxicolous lichens

Abstract: 4 Laboratorio analisi scientifica, Direzione ricerca e progetti cofinanziati, Soprintendenza per i beni e le attività culturali, Regione Autonoma Valle d'Aosta -Piazza Narbonne 3, 11100, Aosta, Italy AbstractRelationships between reproductive strategies and population spatial structure have been often suggested for lichens, but still not supported with experimental aerobiological data. For the first time, this study couples aerobiological investigations on meiospore dispersal by Caloplaca crenulatella (Nyl.) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Other studies have shown that species with spore sizes differing by one order of magnitude can have differences in ejection of two orders of magnitude, with those species with a smaller spore size ejecting more spores (Morando et al 2017). In contrast to the study of Morando et al (2017), we used two species of the same genus, which indicates that the reproductive strategies of genetically proximal species can differ substantially. Parmelina carporrhizans ejected upward fewer spores of greater size (and therefore with more reserve nutrients) and had a higher level of germination success in several culture media, while P. quercina ejected a greater number of smaller spores with lower germination success.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have shown that species with spore sizes differing by one order of magnitude can have differences in ejection of two orders of magnitude, with those species with a smaller spore size ejecting more spores (Morando et al 2017). In contrast to the study of Morando et al (2017), we used two species of the same genus, which indicates that the reproductive strategies of genetically proximal species can differ substantially. Parmelina carporrhizans ejected upward fewer spores of greater size (and therefore with more reserve nutrients) and had a higher level of germination success in several culture media, while P. quercina ejected a greater number of smaller spores with lower germination success.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that P. carporrhizans and P. quercina could be used as models to test the "number-size theory" in lichens. Other studies have shown that species with spore sizes differing by one order of magnitude can have differences in ejection of two orders of magnitude, with those species with a smaller spore size ejecting more spores (Morando et al 2017). In contrast to the study of Morando et al (2017), we used two species of the same genus, which indicates that the reproductive strategies of genetically proximal species can differ substantially.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Giordani et al (2016, with refs therein), we selected traits associated with reproduction and ecophysiology (Table 3). Several traits play a decisive role in the phases of dispersal and establishment of new thalli: most of them include attributes related to morphological characteristics of the spores, such as their shape, number, dimension and color (Armstrong 1981; Morando et al 2017). Some eco-physiological functions, such as substrate colonization, evapotranspiration or photon absorption, are strictly related to lichen growth form (Palmqvist 2000), whereas some features (e.g.…”
Section: Functional Traits and Statistical Analysesmentioning
confidence: 99%